ANALISIS HASIL STRATEGI PEMASARAN STIE WIYATAMANDALA PADA MASA PANDEMI COVID-19 - Allan Yuda Patria Lai Wie (STIE Wiyatamandala, 2023)
This research was conducted to discover students’ responses to STIE Wiyatamandala’s marketing actions, especially during the COVID-19 Pandemic; and to determine whether the marketing decisions were right or not. This study replicates a previous study conducted by Martin Sone Kwang in 2019. The study uses a qualitative research method to explain how service marketing mix influences choice in all four batches of STIE Wiyatamandala’s students, respectively. A minimum of 13 respondents per batch were picked using a non-probability sampling technique, with open-ended structured questions used during the interview process. The result shows different opinions on different batches, with price and physical evidence as the main determinants in shaping students’ choices. The study also showed that most of the marketing actions taken have the desired effect.